Deficits in N-Methyl-D-Aspartate Receptor Function and Synaptic Plasticity in Hippocampal CA1 in APP/PS1 Mouse Model of Alzheimer’s Disease - Xu, Le; Zhou, Yiying; Hu, Linbo; Jiang, Hongde; Dong, Yibei; Shen, Haowei; Lou, Zhongze; Yang, Siyu; Ji, Yunxin; Ruan, Liemin; Zhang, Xiaoqin (Frontiers in Aging Neuroscience, 2021)
The N-methyl-D-aspartate receptor is a critical molecule for synaptic plasticity and cognitive function. Impaired synaptic plasticity is thought to contribute to the cognitive impairment associated with Alzheimer’s disease (AD). However, the neuropathophysiological alterations of N-methyl-D-aspartate receptor (NMDAR) function and synaptic plasticity in hippocampal CA1 in transgenic rodent models of AD are still unclear. In the present study, APP/PS1 mice were utilized as a transgenic model of AD, which exhibited progressive cognitive impairment including defective working memory, recognition memory, and spatial memory starting at 6 months of age and more severe by 8 months of age. We found an impaired long-term potentiation (LTP) and reduced NMDAR-mediated spontaneous excitatory postsynaptic currents (sEPSCs) in the hippocampal CA1 of APP/PS1 mice with 8 months of age. Golgi staining revealed that dendrites of pyramidal neurons had shorter length, fewer intersections, and lower spine density in APP/PS1 mice compared to control mice. Further, the reduced expression levels of NMDAR subunits, PSD95 and SNAP25 were observed in the hippocampus of APP/PS1 mice. These results suggest that NMDAR dysfunction, impaired synaptic plasticity, and disrupted neuronal morphology constitute an important part of the neuropathophysiological alterations associated with cognitive impairment in APP/PS1 mice.